(3JaUjd QSGFd GdTjYI Edi JMUjd eSGFd GdTQjYIs - (3eMeO Hf GdMSf Hf Ydj GdYGedj , GdMQ GdYGedj,J (B1104 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH ehGfY GdGQK s
(3BNQgG (B:s
(3jfJgi HcJGH GdfSH hGdCdbGH s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B204s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B311 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B15 - (3U (B336 s
Keywords: (3abg GdePGgH GdCNQis